2017
DOI: 10.1186/s12967-017-1256-y
|View full text |Cite
|
Sign up to set email alerts
|

The clinical importance of tumour-infiltrating macrophages and dendritic cells in periampullary adenocarcinoma differs by morphological subtype

Abstract: BackgroundDendritic cells (DC) and tumour-associated macrophages (TAM) are essential in linking the innate and adaptive immune response against tumour cells and tumour progression. These cells are also potential target for immunotherapy as well as providing a handle to investigate immune status in the tumour microenvironment. The aim of the present study was to examine their impact on prognosis and chemotherapy response in periampullary adenocarcinoma, including pancreatic cancer, with particular reference to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 33 publications
2
12
0
Order By: Relevance
“…The literature to date on the prognostic significance of MARCO in cancer is sparse. Sun et al (22) reported that a decreased expression of MARCO was associated with tumor progression and poor prognosis in hepatocellular carcinoma and Lundgren et al (23) showed that high density of MARCO + TAMs in certain subtypes of periampullary pancreatic cancer predicted shorter survival. To the best of our knowledge, the expression and prognostic impact of MARCO in GE adenocarcinoma has not yet been reported.…”
Section: Discussionmentioning
confidence: 99%
“…The literature to date on the prognostic significance of MARCO in cancer is sparse. Sun et al (22) reported that a decreased expression of MARCO was associated with tumor progression and poor prognosis in hepatocellular carcinoma and Lundgren et al (23) showed that high density of MARCO + TAMs in certain subtypes of periampullary pancreatic cancer predicted shorter survival. To the best of our knowledge, the expression and prognostic impact of MARCO in GE adenocarcinoma has not yet been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Hilly et al [18] reported that higher CD1a + DCs in ltration around the tumor was associated with a higher risk of recurrence in surgically treated cases of early squamous cell carcinoma of the tongue. Lundgren et al [19] reported that a high density of in ltrating CD1a + DCs is an unfavorable prognostic factor in the pancreato-biliary type of periampullary adenocarcinoma. One of the possible reasons for this discrepancy in ndings is the widely varying methods used to evaluate CD1a + DCs in the previous series.…”
Section: Discussionmentioning
confidence: 99%
“…Comprehensive informed consent for the use of resected tissue for research was obtained from all patients, and the study protocol was approved by the Ethics Committee of the Faculty of Medicine at Saga University (No. 2020-04-R- 19).…”
Section: Patientsmentioning
confidence: 99%
“…Deficient MMR (dMMR) was defined as negative staining for MLH1, PMS2, MSH2 or MSH6, and proficient MMR (pMMR) was defined as positive staining for all four MMR proteins. Immunohistochemical analysis of CD3 + lymphocytes, CD56 + natural killer (NK)/NKT cells and CD68 + and CD163 + macrophages had been performed previously [ 27 , 28 ]. For immunohistochemical analysis of FoxP3 and CD8 + T cells, 4 μm TMA-sections were automatically pre-treated using the PT Link system and then stained in an Autostainer Plus (Dako; Glostrup, Denmark) with the anti-FoxP3 antibody (clone 236A/E7, mouse, dilution 1:200, Abcam, Cambridge, UK), and the anti-CD8 antibody (clone C8/144B, mouse; dilution, 1:50; product M7103; Dako).…”
Section: Methodsmentioning
confidence: 99%